Urea transport-defective strains of Saccharomyces cerevisiae. - Sumrada, R (1976)
Experiments characterizing the urea active transport system in Saccharomyces cerevisiae indicate that (i) formamide and acetamide are strong competitive inhibitors of urea accumulation, (ii) uptake is maximal at pH 3.3 and is 80% inhibited at pH 6.0, and (iii) adenosine 5'-triphosphate generated by glycolysis in conjunction with formation of an ion gradient is likely the driving force behind urea transport. Mutant strains were isolated that are unable to accumulate urea at external concentrations of 0.25 mM. These strains also exhibit a depressed growth rate on 10 mM urea, indicating existence of a relationship between the active transport and facilitated diffusion modes of urea uptake.